2023
DOI: 10.1186/s12879-023-08033-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of eight lateral flow tests for the detection of anti-SARS-CoV-2 antibodies in a vaccinated population

Abstract: Background Rapid determination of an individual’s antibody status can be beneficial in understanding an individual’s immune response to SARS-CoV-2 and for initiation of therapies that are only deemed effective in sero-negative individuals. Antibody lateral flow tests (LFTs) have potential to address this need as a rapid, point of care test. Methods Here we present a proof-of-concept evaluation of eight LFT brands using sera from 95 vaccinated indiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…When utilized related to symptomatology, a determination of contamination might be conceivable. Fast antigen test using anti-CoV antibodies rather than immobilized viral antigen, allowing for a more easy assessment of the current disease [ 151 ].…”
Section: Computational Framework For Covid-19 Diagnostics and Therape...mentioning
confidence: 99%
“…When utilized related to symptomatology, a determination of contamination might be conceivable. Fast antigen test using anti-CoV antibodies rather than immobilized viral antigen, allowing for a more easy assessment of the current disease [ 151 ].…”
Section: Computational Framework For Covid-19 Diagnostics and Therape...mentioning
confidence: 99%
“…A very recent study assessed the sensitivity of eight LFIAs in post-vaccinated individuals and found that the sensitivity increased from dose one to dose two in six out of eight LFIAs [127] . Three tests detecting anti-spike antibodies achieved 100% sensitivity at dose two, compared with a chemiluminescent microparticle immunoassay [127] .…”
Section: Lfia and Response To Vaccinationmentioning
confidence: 99%
“…A very recent study assessed the sensitivity of eight LFIAs in post-vaccinated individuals and found that the sensitivity increased from dose one to dose two in six out of eight LFIAs [127] . Three tests detecting anti-spike antibodies achieved 100% sensitivity at dose two, compared with a chemiluminescent microparticle immunoassay [127] . Another recent study showed that a LFIA (Humasis®, Anyang, South Korea) was able to detect anti-spike antibodies in plasma samples of vaccinated subjects with an accuracy comparable to ELISA, and the strength of label bands correlated with antibody concentrations, although effective protection against infection was not assessed [128] .…”
Section: Lfia and Response To Vaccinationmentioning
confidence: 99%